Design Determinants of Building Envelope for Sustainable Built Environment: A Review (International Journal of Built Environment and Sustainability, 2016)
Building envelope separates indoor environment form outside environment as well as provides a comfortable indoor environment through an appropriate balance of passive and active technologies. Building envelopes and its components are designed with respect to environmental, technological, socio-cultural, functional and aesthetic determinants. In contemporary scenario a major concern is to get a comfortable indoor environment in respect of thermal, visual and psychological comfort.  Further innovation in designing and construction of contemporary building envelope and its components is likely to be developed rapidly. Designing of buildings and its envelope have a major focus on making buildings sustainable by reducing energy consumption without compromising on user’s comfort. This creates a challenge to the designer and engineers to study and monitor the impact on performance of built form design determinants. This paper aims to describe and highlight the role of design determinants in building envelope and in its various components to achieve sustainable built environment. Study has described the difference in terms “energy efficiency and sustainability” in buildings and built spaces for users through the review of definitions and past researches. Further design concept and technology discussed through relevant examples of various typologies of building envelope system and described the parameters of building envelope’s transparent and opaque components for evaluation. This study is an attempt to describe the integration of design determinants like environmental, technological, socio- cultural, functional and aesthetic in building envelope and its components in making efficient and sustainable built form and space as per user comfort. The paper concludes with meaningful recommendations for sustainable development in designing future building envelopes.